1973
DOI: 10.1111/j.1365-2265.1973.tb01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Secretion of the Gonadotrophins, Prolactin, Growth Hormone, Thyrotrophin and Corticosteroids in Man: The Effects of Lh/Fsh‐rh, TRH and Hypoglycaemia Alone and in Combination

Abstract: SUMMARY The interaction between the mechanisms involved in the LH, FSH, growth hormone, prolactin, ACTH and TSH responses to the synthetic LH and FSH releasing hormone, thyrotrophin releasing hormone and insulin induced hypoglycaemia was studied in twelve normal male volunteers. Each subject acted as his own control and the test procedures were performed individually and in combination. The simultaneous administration of one releasing hormone with another or with insulin in no way modified the hormonal respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

1975
1975
2001
2001

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(37 citation statements)
references
References 11 publications
(7 reference statements)
2
34
0
1
Order By: Relevance
“…In contrast, several groups of workers have been unable to show consistent changes in prolactin levels during the cycle (Hwang et al, 1971;Tyson and Friesen, 1973;Jaffe et al, 1973;McNeilly, Evans and Chard, 1973;Ehara eta., 1973;McNeilly and Chard, 1974 (Ehara etal., 1973;McNeilly and Chard, 1974), and prolactin secretion appeared to occur in a spike-like manner, similar to that seen in normal male subjects (Mortimer et al, 1973;McNeilly and Hagen, 1974). In addition, no changes in prolactin levels occur when gonadotrophins are elevated in postmenopausal women (McNeilly, Ormston and Hall, unpublished observations), after clomiphene in normal men (Thorner et al, 1974) (Zarate et al, 1972), or galactorrhoea (Thorner et al, 1974) (Thorner et al, 1974a), indicating removal of a peripheral block to steroidogenesis.…”
Section: Prolactin and The Menstrual Cyclesupporting
confidence: 71%
“…In contrast, several groups of workers have been unable to show consistent changes in prolactin levels during the cycle (Hwang et al, 1971;Tyson and Friesen, 1973;Jaffe et al, 1973;McNeilly, Evans and Chard, 1973;Ehara eta., 1973;McNeilly and Chard, 1974 (Ehara etal., 1973;McNeilly and Chard, 1974), and prolactin secretion appeared to occur in a spike-like manner, similar to that seen in normal male subjects (Mortimer et al, 1973;McNeilly and Hagen, 1974). In addition, no changes in prolactin levels occur when gonadotrophins are elevated in postmenopausal women (McNeilly, Ormston and Hall, unpublished observations), after clomiphene in normal men (Thorner et al, 1974) (Zarate et al, 1972), or galactorrhoea (Thorner et al, 1974) (Thorner et al, 1974a), indicating removal of a peripheral block to steroidogenesis.…”
Section: Prolactin and The Menstrual Cyclesupporting
confidence: 71%
“…FSHand PRL (16)(17)(18). It was reported that this TRHincrease was the etiologic factor in the so-called "feedback" mechanism, and the condition came to be called "overlap syndrome" ( 16).…”
Section: Discussionmentioning
confidence: 99%
“…A central effect of hyperprolactinaemia on gonadotrophin secretion is suggested by the modification of pulsatile secretion,especiallyofLH (Boyer et al, 1974;Bohnet et al, 1976), and by the interference with feedback control (Glass et al, 1975). However, an initial assumption that gonadotrophin secretion is deficient has not been borne out by our experience, since our hyperprolactinaemic patients have normal gonadotrophin levels and a normal or even exaggerated response to GnRH (Mortimer et al, 1973;Thorner et al, 1974;Child et al, 1975). There is also the possibility that prolactin may in some way interfere with the action of the gonadotrophins on the gonads, in which case lowering the prolactin level should rapidly restore gonadal function to normal.…”
Section: Mechanism Of Hypogonadism In Hyperprolactinaemiamentioning
confidence: 69%